2009
DOI: 10.1152/jn.00243.2009
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Temporal Synchrony as a Binding Cue for Visual Persistence in Early Visual Areas: An fMRI Study

Abstract: We examined the role of temporal synchrony-the simultaneous appearance of visual features-in the perceptual and neural processes underlying object persistence. When a binding cue (such as color or motion) momentarily exposes an object from a background of similar elements, viewers remain aware of the object for several seconds before it perceptually fades into the background, a phenomenon known as object persistence. We showed that persistence from temporal stimulus synchrony, like that arising from motion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…Some activation was seen in V1, V3A/B and hV4. Ferber et al (2003) found an increased hemodynamic response in LO from movement-triggered persistence that lasted a few seconds, and Wong et al (2009) were able to produce similar effects by briefly displaying a segmented figure upon a background of random line segments.…”
Section: Further Evaluation Of Locusmentioning
confidence: 83%
“…Some activation was seen in V1, V3A/B and hV4. Ferber et al (2003) found an increased hemodynamic response in LO from movement-triggered persistence that lasted a few seconds, and Wong et al (2009) were able to produce similar effects by briefly displaying a segmented figure upon a background of random line segments.…”
Section: Further Evaluation Of Locusmentioning
confidence: 83%
“…Previous studies defined persistence-related fMRI responses as those that were greater in the persist condition as compared with the vanish condition following the offset of figure motion, because the stimuli in the two conditions are identical during the motion phase (Strother et al, 2011;Wong et al, 2009;Ferber et al, 2003Ferber et al, , 2005Large et al, 2005). As in these previous studies, whole-brain analyses revealed persistence-related responses in LO (but not adjacent MT+) in all subjects, for all annulus sizes (persist > vanish; always p < 10 −3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, neither of these studies observed decreases in V1 fMRI responses, which one would expect if background suppression is crucial to perceived figure-ground segmentation. Several other fMRI studies reported increased figure-ground fMRI activity in extrastriate visual areas (Wong, Aldcroft, Large, Culham, & Vilis, 2009;Ferber, Humphrey, & Vilis, 2003Large, Aldcroft, & Vilis, 2005;Schira, Fahle, Donner, Kraft, & Brandt, 2004), but these studies also failed to observe fMRI responses corresponding to background suppression in V1. This is surprising because perceived figure-ground boundaries automatically engage attentional mechanisms (Egeth & Yantis, 1997), which are known to produce concomitant enhancement and suppression of neural responses in V1, even in the absence of visual stimulation (Silver, Ress, & Heeger, 2007;Kastner, Pinsk, De Weerd, Desimone, & Ungerleider, 1999).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…A number of functional neuroimaging studies have attempted to identify the neural substrates subserving persistence during SFM (Ferber, Humphrey, & Vilis, 2005;Large, Aldcroft, & Vilis, 2005;Strother et al, 2011;Wong, Aldcroft, Large, Culham, & Vilis, 2009). These studies have revealed that perceptual persistence is associated with sustained activation in the ventral visual pathway, particularly in the object-sensitive lateral occipital complex (LOC; Ferber et al, 2005;Large et al, 2005), as well as in the primary visual cortex (Strother et al, 2011).…”
mentioning
confidence: 99%